2021
DOI: 10.3389/fpubh.2021.609716
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Toward Protective Behavior Engagement During COVID-19 Pandemic in Malaysia: The Role of E-government and Social Media

Abstract: The coronavirus disease 2019 (COVID-19) pandemic is still evolving and affecting millions of lives. E-government and social media have been used widely during this unprecedented time to spread awareness and educate the public on preventive measures. However, the extent to which the 2 digital platforms bring to improve public health awareness and prevention during a health crisis is unknown. In this study, we examined the influence of e-government and social media on the public's attitude to adopt protective be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Studies have shown that mass media campaigns (power of the video) urge the public to adopt healthy behaviors that can positively influence people’s behaviors and prevent harmful practices in society. Furthermore, mass media channels can increase public awareness and individual participation in health care issues (Mat Dawi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that mass media campaigns (power of the video) urge the public to adopt healthy behaviors that can positively influence people’s behaviors and prevent harmful practices in society. Furthermore, mass media channels can increase public awareness and individual participation in health care issues (Mat Dawi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that mass media campaigns (power of the video) urge the public to adopt healthy behaviors that can positively influence people's behaviors and prevent harmful practices in society. Furthermore, mass media channels can increase public awareness and individual participation in health care issues (Mat Dawi et al, 2021). Furthermore, all mass media channels which were used by public authorities have contributed effectively to raise public health knowledge and promoting behavioral social change against Coronavirus (COVID-19 pandemic) in Jordan.…”
Section: Discussionmentioning
confidence: 99%
“…According to his study, interactive communication, social media, mobile and web-based platforms will change the means of the e-government portal. In fact, the importance of digital transformation of public services and (Priyono et al, 2020 andIivari et al, 2020;Nagel, 2020;Soto-Acosta, 2020;€ Onc€ u et al, 2021;Yıldırım et al, 2021) the need for the e-government portal has been realized (Yasir et al, 2020;Mat Dawi et al, 2021) during COVID-19 pandemic. The recent trend of the e-government portal design is mostly seen as citizen-user friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Protective Behavior. In (Mat et al, 2021) the argument is stated that individual behavior in adopting protective behavior is more important than government action in controlling the spread of COVID-19. Human behavior is paramount to tackle a pandemic.…”
Section: H2: Illustrating the Coronavirus With The Human Scheme (Corona Anthropomorphic) Increases Consumers' Fear Of The Effects Of The mentioning
confidence: 99%